Clinical Efficacy of Bladder Neck Injection of Botulinum Toxin A in Treating Neurogenic and Non-Neurogenic Voiding Dysfunctions Due to Bladder Neck Dysfunction - Yu-Shuang Lee; Yu-Khun Lee; Tien-Lin Chang; Cheng-Ling Lee; Sheng-Fu Chen; Jia-Fong Jhang; Yuan-Hong Jiang; Hann-Chorng Kuo (Toxins, 2025)
Bladder neck dysfunction (BND) is a pathophysiology associated with voiding dysfunction in patients with neurogenic or non-neurogenic voiding dysfunction. Botulinum toxin A (BoNT-A) injection is a minimally invasive alternative for treating bladder outlet dysfunction; however, its efficacy for BND has not been well established. In this retrospective study, 41 patients with videourodynamic study-confirmed BND who failed medical therapy received a transurethral bladder neck injection of 100-U BoNT-A. Treatment outcomes were assessed using the Global Response Assessment. After BoNT-A injection, the patients were followed up and subsequent urological management was recorded. At 6 months, 65.9% of the patients reported satisfactory outcomes (26.8% successful and 39.0% improved). Patients with non-neurogenic BND had the highest satisfaction rate, higher than those with neurogenic BND (NBND) with and without detrusor sphincter dyssynergia (DSD). Among patients without detrusor acontractility (DA), a higher bladder outlet obstruction index predicted treatment failure. Patients with pure BND confirmed by urodynamics may benefit more from BoNT-A injections, whereas those with high baseline voiding detrusor pressure or spinal cord injury with detrusor sphincter dyssynergia may have less favorable results. Bladder neck BoNT-A injections for treating BND-associated voiding dysfunction did not achieve very successful outcomes. Only 26.8% of the patients had successful treatment outcomes, while 39.0% had improved outcomes and 34.1% failed the treatment.